Dietary reversal of neuropathy in a murine model of prediabetes and metabolic syndrome - Lucy M. Hinder; Phillipe D. O'Brien; John M. Hayes; Carey Backus; Andrew P. Solway; Catrina Sims-Robinson; Eva L. Feldman (The Company of Biologists, 2017)
Patients with metabolic syndrome, which is defined as obesity, dyslipidemia, hypertension and impaired glucose tolerance (IGT), can develop the same macro- and microvascular complications as patients with type 2 diabetes, including peripheral neuropathy. In type 2 diabetes, glycemic control has little effect on the development and progression of peripheral neuropathy, suggesting that other metabolic syndrome components may contribute to the presence of neuropathy. A parallel phenomenon is observed in patients with prediabetes and metabolic syndrome, where improvement in weight and dyslipidemia more closely correlates with restoration of nerve function than improvement in glycemic status. The goal of the current study was to develop a murine model that resembles the human condition. We examined longitudinal parameters of metabolic syndrome and neuropathy development in six mouse strains/genotypes (BKS-wt, BKS-Leprdb/+, B6-wt, B6-Leprdb/+, BTBR-wt, and BTBR-Lepob/+) fed a 54% high-fat diet (HFD; from lard). All mice fed a HFD developed large-fiber neuropathy and IGT. Changes appeared early and consistently in B6-wt mice, and paralleled the onset of neuropathy. At 36 weeks, B6-wt mice displayed all components of the metabolic syndrome, including obesity, IGT, hyperinsulinemia, dyslipidemia and oxidized low density lipoproteins (oxLDLs). Dietary reversal, whereby B6-wt mice fed a HFD from 4-20 weeks of age were switched to standard chow for 4 weeks, completely normalized neuropathy, promoted weight loss, improved insulin sensitivity, and restored LDL cholesterol and oxLDL by 50% compared with levels in HFD control mice. This dietary reversal model provides the basis for mechanistic studies investigating peripheral nerve damage in the setting of metabolic syndrome, and ultimately the development of mechanism-based therapies for neuropathy.